Pengaruh Penambahan Phenethylammonium Iodida (PEAI) terhadap Struktur dan Sifat Optik Lapisan Perovskite Solar Cell FAPbI3 - Manda, Poni Dwi; Dahlan, Dahyunir; Harmadi, Harmadi; Umar, Akrajas Ali (Jurnal Fisika Unand, 2025)
This study explores the effect of doping phenethylanimum iodide (PEAI) on grain size and absorption ability in the perovskite formanidinium lead iodide (FAPbI3) layer. FAPbI3 was chosen as the object of study because of its potential application in perovskite-based solar cell technology. In this experiment, the FAPbI3 perovskite layer was prepared with a PEAI doping variation using a two-stage spin-coating method. Ultraviolet-visible (UV-Vis) spectrum analysis showed that the perovskite layer has typical optical absorption characteristics at a wavelength of 780 nm, with a measured energy gap value of 1.48 eV at a PEAI concentration of 2 mg/ml. In addition, the surface morphology of FAPbI3 showed an increase in grain size along with the addition of PEAI doping, where the optimal grain size was recorded at a doping of 2 mg/ml with a size of 0.54 ± 0.03 μm and a smooth and homogeneous morphology. These findings are expected to make a significant contribution to the development of more efficient and stable solar cells